2002
DOI: 10.1126/science.1073031
|View full text |Cite
|
Sign up to set email alerts
|

Myelin-Associated Glycoprotein as a Functional Ligand for the Nogo-66 Receptor

Abstract: Axonal regeneration in the adult central nervous system (CNS) is limited by two proteins in myelin, Nogo and myelin-associated glycoprotein (MAG). The receptor for Nogo (NgR) has been identified as an axonal glycosyl-phosphatidyl-inositol (GPI)-anchored protein, whereas the MAG receptor has remained elusive. Here, we show that MAG binds directly, with high affinity, to NgR. Cleavage of GPI-linked proteins from axons protects growth cones from MAG-induced collapse, and dominant-negative NgR eliminates MAG inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
362
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 524 publications
(381 citation statements)
references
References 21 publications
10
362
5
Order By: Relevance
“…However, this peptide could also be interfering with the ability of Mag and Omgp to bind to Ngr. library, and they found a new ligand that was shown to be Mag 35 . At the same time, our group had co-precipitated the two proteins and had also identified Ngr as a receptor for Mag 36 .…”
Section: Receptors For Inhibitors Of Axonal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this peptide could also be interfering with the ability of Mag and Omgp to bind to Ngr. library, and they found a new ligand that was shown to be Mag 35 . At the same time, our group had co-precipitated the two proteins and had also identified Ngr as a receptor for Mag 36 .…”
Section: Receptors For Inhibitors Of Axonal Growthmentioning
confidence: 99%
“…Given that Nogo-66, Mag and Omgp all interact with Ngr with about the same relatively high affinity 28,32,35,36 , and assuming that they are the only inhibitors (but see later discussion on amino-Nogo) and that there is only one receptor complex, the contribution that each makes depends on two factors -their relative abundance in myelin, and the likelihood of a growth cone encountering each inhibitor as it attempts to regenerate. Mag represents 1 % and 0.1 % of the total myelin protein in the CNS and PNS, respectively, and it is found mostly in the inner myelin loop in the CNS 23,49 .…”
Section: Nogo-a Omgp Magmentioning
confidence: 99%
“…Nogo-66, together with both MAG and OMgp, bind and activate the same receptor, the neuronal, glycosyl-phosphatidyl-inositol (GPI)-anchored Nogo-66 Receptor (NgR; Fournier et al, 2001;Domeniconi et al, 2002;Liu et al, 2002a;Wang et al, 2002a) with additional molecules including p75 NTR , Lingo-1 and TAJ/TROY required for signaling (Mi et al, 2004;Shao et al, 2005;Park et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A competitive antagonist of NgR, NEP1-40, blocks the inhibitory action of myelin in vitro 51 and enhances both growth of supraspinal axons and functional recovery when administered intrathecally or systemically after thoracic hemisection. 51,52 Another antagonist, NgREcto, is a soluble, truncated form of NgR, which has been shown to alleviate inhibition of both Nogo and myelin in vitro (Fournier et al, 2002). Recent work from our group examines the effects of NgR activity using a different form of soluble NgR in vivo; 53 in these experiments, we found that NgR antagonism augmented rhizotomy-induced sprouting of both descending monoaminergic axons and peptidgeric primary afferents in the cervical dorsal horn.…”
Section: Myelin and Myelin Signaling: An Inhibitory Chorus Linementioning
confidence: 86%
“…[47][48][49][50] As an apparent point of convergence in inhibitory signaling, NgR has taken the stage as a target of strategies aimed at increasing plasticity in the injured spinal cord. A competitive antagonist of NgR, NEP1-40, blocks the inhibitory action of myelin in vitro 51 and enhances both growth of supraspinal axons and functional recovery when administered intrathecally or systemically after thoracic hemisection.…”
Section: Myelin and Myelin Signaling: An Inhibitory Chorus Linementioning
confidence: 99%